THE IMPLEMENTATION OF MAKE A MATCH METHOD TO IMPROVE WRITING DESRIPTIVE TEXT AT TENTH GRADE STUDENTS IN SMK JABIR AL-HAYYAN - Mahmud Yusuf; Hasanudin Hasanudin (IKIP Siliwangi, 2020)
Based on the phenomena that students have difficulties in writing descriptive text, the students could not write because do not have any ideas when they are asked to write. So, they need some ways which could help them in writing. The problems in writing can be solved by implementing some strategies in teaching writing. One of approach that teacher can use to help students write a good text is MAM. The main objective of this study is find out if MAM can improve students’ ability in writing descriptive text. The research method used is quantitative research, specifically quantitative with one group pretest-posttest design. The sample take two class at tenth grade students of SMK Jabir Al-Hayyan in academic year 2019/2020. The data had been obtained in post-test of experimental class were: the highest score was 96, the lowest score was 62, and the mean score was 80.50. Post-test of control class were: the highest score was 89, the lower score was 60, and the mean score was 71.54. It can be seen from the data showed that students’ score in experimental class was highest than control class. It means that using make a match method was effective, easier, and more understable to be applied in teaching and learning process, especially in writing descriptive text. Keywords: Improve, Make A Match Method, Writing Descriptive Text